Targeted mRNA demethylation using an engineered dCas13b-ALKBH5 fusion protein. Issue 10 (1st May 2020) - Li, Jiexin; Chen, Zhuojia; Chen, Feng; Xie, Guoyou; Ling, Yuyi; Peng, Yanxi; Lin, Yu; Luo, Nan; Chiang, Cheng-Ming; Wang, Hongsheng
Abstract: Studies on biological functions of N 6 -methyladenosine (m 6 A) modification in mRNA have drawn significant attention in recent years. Here we describe the construction and characterization of a CRISPR–Cas13b-based tool for targeted demethylation of specific mRNA. A fusion protein, named dm 6 ACRISPR, was created by linking a catalytically inactive Type VI-B Cas13 enzyme from Prevotella sp. P5–125 (dPspCas13b) to m 6 A demethylase AlkB homolog 5 (ALKBH5). dm 6 ACRISPR specifically demethylates m 6 A of targeted mRNA such as cytochrome b5 form A (CYB5A) to increase its mRNA stability. It can also demethylate β-catenin-encoding CTNNB1 mRNA that contains multiple m 6 A sites to trigger its translation. In addition, the dm 6 ACRISPR system incurs efficient demethylation of targeted epitranscriptome transcripts with limited off-target effects. Targeted demethylation of transcripts coding for oncoproteins such as epidermal growth factor receptor (EGFR) and MYC can suppress proliferation of cancer cells. Together, we provide a programmable and in vivo manipulation tool to study mRNA modification of specific genes and their related biological functions.